The photoluminescence of isolated and paired Bi3+ ions in layered LnOCl crystals: a first-principles study. Issue 22 (31st May 2022) - Chen, Qiaoling; Feng, Zhaoyang; Liu, MingZhe; Lou, Bibo; Ma, Chong-Geng; Duan, Chang-Kui
Abstract : Luminescent n s 2 centers have shown great potential for applications as phosphors and scintillators and intervalent charge transfer transitions are explored. Abstract : Luminescent n s 2 centers have shown great potential for applications as phosphors and scintillators. First-principles calculations based on density functional theory are performed to systematically analyze the luminescent centers of isolated and paired Bi 3+ (6s 2 ) ions in layered LnOCl (Ln = Y, Gd, La) crystals. The spin–orbit coupling and orbital hybridization both show important effects on the luminescence properties. The luminescence of the isolated Bi ion is confirmed as the interconfigurational transition of 3 P0, 1 → 1 S0 . For the Bi pair, the adiabatic potential energy surfaces are calculated and the charge transfer excited state is the most stable, which accounts for the visible emission of a large Stokes shift. Furthermore, the electron–hole pair separation, absorption, excitonic state and emission of the material with fully-concentrated Bi 3+, BiOCl, are discussed. This study shows that the first-principles calculations can serve as an effective tool for the photoluminescence analysis and engineering of materials activated with isolated, paired and even fully-concentrated n s 2 ions.